Improved modelling of soil NOx emissions in a high temperature agricultural region: role of background emissions on NO2 trend over the US. (6th August 2021) - Wang, Yi; Ge, Cui; Castro Garcia, Lorena; Jenerette, G Darrel; Oikawa, Patty Y; Wang, Jun
Abstract: EPA reports a steady decline of US anthropogenic NO x emissions in 2005–2019 summers, while NO2 vertical column densities (VCDs) from the OMI satellite over large spatial domains have flattened since 2009. To better understand the contributing factors to a flattening of the OMI NO2 trends, we investigate the role of soil and lightning NOx emissions on this apparent disagreement. We improve soil NO x emissions estimates using a new observation-based temperature response, which increases the linear correlation coefficient between GEOS-Chem simulated and OMI NO2 VCDs by 0.05–0.2 over the Central US. Multivariate trend analysis reveals that soil and lightning NO x combined emissions trends change from −3.95% a −1 during 2005–2009 to 0.60% a −1 from 2009 to 2019, thereby rendering the abrupt slowdown of total NO x emissions reduction. Non-linear inter-annual variations explain 6.6% of the variance of total NO x emissions. As background emissions become relatively larger with uncertain inter-annual variations, the NO2 VCDs alone at the national scale, especially in the regions with vast rural areas, will be insufficient to discern the trend of anthropogenic emissions.